(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
The protracted conflict between Israel-Palestine continues to give rise to serious humanitarian issues, particularly concerning human rights violations against affected civilians. This research seeks to explore how far international law, particularly international humanitarian law and its institutions, such as the International Criminal Court (ICC) can provide legal protection and enforce accountability for war crimes. Using normative legal research and a case study approach, this research explores the effectiveness of legal instruments like the Geneva Conventions and the Rome Statute in addressing such violations. Findings indicate that although international legal frameworks are in place, enforcement remains weak due to political obstacles and the limited authority of international bodies. This paper argues that a stronger, more independent mechanism is essential to prosecute perpetrators and uphold justice for victims. Strengthening international legal enforcement is crucial to achieving sustainable peace and ensuring that human rights are genuinely protected in armed conflicts. Konflik berkepanjangan antara Israel dan Palestina terus memunculkan persoalan kemanusiaan yang serius, terutama terkait pelanggaran hak asasi manusia terhadap warga yang terdampak. Disini, penelitian ditujukan untuk mengulas sejauh mana hukum internasional (HI), khususnya hukum humaniter dan lembaga seperti Mahkamah Pidana Internasional (ICC), dalam mengedepankan hak asasi manusia atas kejahatan perang. Metode penelitian hukum normatif serta pendekatan kasus, studi ini menelaah efektivitas dokumen hukum internasional semacam Konvensi di Jenewa dan Statuta dari Roma dalam merespons berbagai pelanggaran. Temuan dalam penelitian berisikan bahwa meski mekanisme hukum yang ada sudah cukup solid, penegakannya sering kali terkendala oleh faktor politik dan lemahnya kewenangan lembaga internasional. Oleh karena itu, dibutuhkan mekanisme yang lebih tegas dan independen dalam menindak pelaku kejahatan serta memastikan perlindungan terhadap korban konflik. Penegakan hukum yang adil menjadi kunci menuju perdamaian yang berkelanjutan.